Pendekatan Min-Max Dalam Strategi Perencanaan Bahan Baku Plant Bm Gresik Guna Meminimalisir Biaya Persediaan Bahan Baku - Nirwana, Jean Audi Cahaya; Herlina, Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT Varia Usaha Beton is a reliable and reliable concrete company. Every day, PT. Varia Usaha Beton always gets orders for various paving products from various cities according to the products available at PT. Varia Usaha Concrete Plant BM Gresik. PT. Varia Usaha Beton Plant BM Gresik uses 5 main raw materials for paving production, namely fly ash, 5-10 stone, 0/5 stone, cement and Lumajang sand. Raw material planning at PT. The BM Gresik Concrete Plant Business Varia often goes out of control, resulting in shortages (stock out) or excess raw materials (overstock). Uncontrolled raw materials sector results in high inventory costs. The aim of this research is to plan raw material requirements and minimize costs using the min-max method by determining the optimal order quantity, minimum and maximum stock that must be met, reorder pont, safety stock, and total inventory cost. With this research using the min-max method, results were obtained that minimized inventory costs. For fly ash raw materials, total inventory cost efficiency results were obtained at 3%, for 5-10 stone raw materials, total inventory cost efficiency results were obtained at 63%, for 0/5 raw materials, total inventory cost efficiency results were 6%. For cement, total inventory cost efficiency results were obtained at 15%, and for Lumajang sand raw materials, total inventory cost efficiency results were obtained at 20%.